1996
DOI: 10.3928/1542-8877-19960401-04
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Topographic Changes and Induced Astigmatism Resulting From Superior and Temporal Scleral Pocket Incisions

Abstract: * BACKGROUND AND OBJECTIVE: To determine the corneal topographic changes that are induced by superior and temporal 5-mm sclera! pocket incisions. * PATIENTS AND METHODS: The authors retrospectively reviewed the records of 43 patients who underwent phacoemulsification with posterior chamber lens implantation through unsutured 5-mm scierai pocket incisions, 24 superiorly and 19 temporally. Corneal curvature was measured using computerized videokeratography, and the induced astigmatism was calculated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…However, the differences between the groups were not statistically significant. [10] In the present study, the SIA in s-MSICS group was 1.43 ± 0.99D and in t-MSICS group it was 0.76 ± 0.66 (p=0.028). A study conducted by Malik et al, showed similar results with superior group having SIA of 1.45 ± 0.738D and temporal group having SIA of 0.75 ± 0.406D.…”
Section: Discussionsupporting
confidence: 45%
“…However, the differences between the groups were not statistically significant. [10] In the present study, the SIA in s-MSICS group was 1.43 ± 0.99D and in t-MSICS group it was 0.76 ± 0.66 (p=0.028). A study conducted by Malik et al, showed similar results with superior group having SIA of 1.45 ± 0.738D and temporal group having SIA of 0.75 ± 0.406D.…”
Section: Discussionsupporting
confidence: 45%